2013
DOI: 10.1080/0972060x.2013.764201
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Essential Oils and Their Combinations with Aluminum Starch Octenylsuccinate on Potato Storage Pathogens

Abstract: S-carvone, L-menthone, peppermint and spearmint oils were tested in vitro against Fusarium coeruleum, F. sambucinum, F. avenaceum, F. oxysporum, Alternaria solani, Rhizoctonia solani, Helminthosporium solani, Phytophthora infestans (A1 and A2 mating types), Phytophthora erythroseptica, Phoma exigua and Pythium ultimum which are causal agents of major potato storage diseases. The majority of these pathogens were completely inhibited due to pure oils, although F. sambucinum, F. avenaceum, A. solani and P. exigua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…They are extracted from more than 17,000 aromatic plants belonging to angiosperm families: Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae and Asteraceae [14], and they have multiple antibacterial, antifungal, antiviral, antiparasitical, insecticidal, medicinal and cosmetic applications [15]. At least 16 different publications [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] presented data on EOs antifungal activities from 35 plants against F. avenaceum (Table 1). All the authors used either agar diffusion methods (paper discs or wells), or an agar dilution method.…”
Section: Introductionmentioning
confidence: 99%
“…They are extracted from more than 17,000 aromatic plants belonging to angiosperm families: Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae and Asteraceae [14], and they have multiple antibacterial, antifungal, antiviral, antiparasitical, insecticidal, medicinal and cosmetic applications [15]. At least 16 different publications [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] presented data on EOs antifungal activities from 35 plants against F. avenaceum (Table 1). All the authors used either agar diffusion methods (paper discs or wells), or an agar dilution method.…”
Section: Introductionmentioning
confidence: 99%
“…L-menthone also has an excellent inhibitory effect on Fusarium sambucinum and Rhizoctonia solani. Many scientists have also found that components synergize when mixed with some antifungal agents [31]. After MEO was made into a nanoemulsion, the inhibitory effect on F. oxysporum was signi cantly improved because the main components, such as menthol, L-menthone, and menthyl acetate in the MNEO, were more abundant than those in MTEO.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium starch octenylsuccinate (ASOS), commonly used in the cosmetic industry as an anticaking agent, has been successfully combined with plant essential oils (from e.g., peppermint and spearmint) and plant terpenes (including l-menthone and S-carvone,) to inhibit several potato storage diseases caused by F. coeruleum, F. sambucinum, F. avenaceum, F. oxysporum, A. solani, R. solani, H. solani, P. infestans, P. erythroseptica, Phoma exigua, and Pythium ultimum. Mixtures of 10 g of ASOS and 4 g or 8 g of essential oils were the most effective in inhibiting these pathogens for periods over 13 or 20 days, respectively, particularly R. solani [84].…”
Section: Enhancing Postharvest Performancementioning
confidence: 97%